Three different kinds of weak C-H⋯O=C inter- and intramolecular interactions in poly(ε-caprolactone) studied by using terahertz spectroscopy, infrared spectroscopy and quantum chemical calculations. (14th February 2018) - Funaki, Chihiro; Yamamoto, Shigeki; Hoshina, Hiromichi; Ozaki, Yukihiro; Sato, Harumi
Abstract: The long range structure of poly( ε -caprolactone) (PCL) has been studied by terahertz (THz) spectroscopy, infrared (IR) spectroscopy and quantum chemical calculations (QCCs). Natural bond orbital (NBO) analysis and the calculation of the interatomic distances between C-H and O=C groups in PCL crystalline indicate that the PCL chain has three kinds of weak intermolecular interactions between the CH2 and C=O groups. In the IR spectra, significant changes due to the influence of hydrogen bondings were observed in the CH2 and C=O stretching vibration regions. The results of QCCs performed by using the Cartesian Coordinate Tensor Transfer (CCT) method to assign the THz spectra of PCL suggest that the peaks at 47 and 67 cm −1 reflect the atomic motions of the C=O + CH2 moiety derived from the weak C-H⋯O=C hydrogen bondings. THz spectroscopy allows us to observe the intermolecular hydrogen bondings of the polymer separately, since hydrogen bondings with different strengths yield different peaks in a THz spectrum. The results of THz and IR spectral analysis, and QCCs all indicate that PCL forms three kinds of weak intermolecular C-H⋯O=C hydrogen bondings between the CH2 and C=O groups. This may be one of the causes for the low melting temperature but high crystallinity of PCL. There are about six interactions in PCL and about sixteen interactions in polyglycolic acid (PGA), within the lamellar thickness. Therefore, it is suggested that the difference in the number of intermolecular interactions within the lamellar thickness leads to the difference in melting points between the two polymers. Graphical abstract: Image 1 Highlights: The long range structure of poly( ε -caprolactone) (PCL) has been studied by THz and IR spectroscopy, and QCCs. NBO analysis indicate PCL chain has three kinds of weak intermolecular interactions between the CH2 and C=O groups. The results of QCCs performed by using the Cartesian Coordinate Tensor Transfer (CCT) method to assign the THz spectra of PCL suggest that the peaks at 47 and 67 cm −1 reflect the atomic motions of the C=O + CH2 moiety derived from weak C-H⋯O=C hydrogen bondings.